Gender Differences at Household Level in Pokhara Metropolitan, Kaski - Subedi, Susmita; Sharma, Ganesh (Journal of Development and Social Engineering, 2024)
Nepalese society is now becoming more egalitarian for men and women, but various forms of gender differences and inequalities still exist, hindering women to properly exercise their rights and freedoms to live a full and happy life. Many such studies were conducted in the past in Nepal, however progress on the matter remains to be understood as various facets of globalization and national level efforts have been influencing existing gender-based differences in the society. This study aims to explore the gender differences in household decision-making in an urban area of Nepal, examining the roles of male and female in decision making of various household issues. Employing a mixed-methods approach, it has triangulated quantitative data gathered through structured questionnaires with qualitative insights obtained from few case studies. The sample consists of 380 households with either male or female heads, and their respective partners or eldest male members from Pokhara-5 along with two qualitative case studies. It was found men still have greater decision-making power or freedom regarding aspects like working outside home, house and land ownership, and performing daily household activities like caring children or elderly, washing, cooking, and cleaning along with in financial decision making, except in government job. Women have unequal share of responsibilities to perform those activities. To promote gender equality at household level, existing policy provisions need to be continued with increased commitment from all stakeholders.